Dealing with non-performing loans during the bank restructuring process in Vietnam: Assessment using the AHP and TOPSIS methods - Tran, Anh Thi Van; Nguyen, Nhung Thi; Tran, Tu Thi Thanh (Gadjah Mada international journal of business, 2020)
This article aims to assess the solutions that have been implemented in Vietnam to deal with non-performing loan(s) (NPLs) in the banking system. By trying to build evaluation criteria through a literature review and an expert survey, as well as using the analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS), this research measures the effectiveness of the resolution of NPLs in Vietnam through many factors. The empirical results show that, in the past, the banking system in Vietnam has not dealt very well with bad debt, as it mostly uses traditional methods such as NPL write-offs by loan loss reserves or the liquidation of collateral. Based on our consideration of the NPLs' resolutions that the Vietnamese banking system has implemented recently, we propose some suggestions to improve the necessary conditions for applying more market-based solutions, such as debt-equity swaps and securitization to thoroughly resolve the NPLs in Vietnam.